Role of Individual Characteristics and Policies in Driving Labor Informality in Vietnam. (Washington, D.C. : International Monetary Fund, 2020)
Using data from the Vietnam Labor Force Survey, this paper takes a granular look at the most salient drivers of labor informality in Vietnam by examining: (i) the nature of labor informality and transitions from formal to informal employment status and the role of worker characteristics; (ii) the empirical likelihood of being in informal employment and the policy determinants of informality using within-in country variation in the business climate and governance; and (iii) whether different policy reforms have a differential impact on workers. Our analysis sheds light on how individual characteristics and policy impediments contribute to high levels of informality and points to the need for a comprehensive agenda to tackle informality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet